Exposure assessment and safety considerations for working with engineered nanoparticles - Ellenbecker, Michael J. (Wiley, 2015)
Addresses health and safety issues associated with workplace Nanoparticle exposures-'Describes methods to evaluate and control worker exposures to engineered nanoparticles-'Provides guidance for concerned EHS professionals on acceptable levels of exposure to nanoparticles-'Includes documentation on best practices to be followed by all researchers when working with engineered nanoparticles-'Describes current knowledge on toxicity of nanoparticles-'Includes coverage on Routes of Exposure for Engineered Nanoparticles.